Raman Spectral Shifts in Naturally Faulted Rocks. (20th October 2021) - Muirhead, D. K.; Kedar, L.; Schito, A.; Corrado, S.; Bond, C. E.; Romano, C.
Abstract: Raman spectral shifts of carbonaceous materials arising from faulted rocks produce varied and complex results. By analyzing faulted and adjacent non‐faulted samples from three discrete localities in France, Italy, and Morocco, we assess changes in specific Raman parameters, including G‐peak width, G‐peak position, and peak intensity ratios. We consistently observe a shift in Raman parameters between faulted and non‐faulted samples; however, the direction and magnitude of this shift varies. Raman peak intensity ratios are shown to both increase and decrease on fault planes. The majority of samples exhibit decreasing peak width and peak position in the faulted samples, but this is not consistent; in two samples an increase is observed, but the shift tends to be small. These data are compared to published Raman spectral shifts from experimental fault data. Our results suggest that fault zone deformation processes may measurably change the carbon nanostructure in faulted rocks. The inconsistent nature of Raman spectral shifts in the fault rock samples analyzed, and those published suggest that a complex set of factors control carbon nanostructure changes in fault rocks. These factors, although not discriminated here, likely include, background temperature, frictional heating, strain, carbonaceous material type, amongst others. We have shown that Raman Spectral shifts occur in faulted rocks with implications for how Raman data are used to predict maximum temperatures in faulted sedimentary rocks. We recognize the potential for a range of fault zone processes to modify Raman spectral shifts, however, systematic sampling across individual fault zones is critical. Plain Language Summary: Faulting in rocks (which can cause earthquakes) can create structural changes to materials at the fault surface. Here we have investigated the effects of faulting on carbon in various localities from France, Italy and Morocco. Carbon can be analyzed using a technique called Raman spectroscopy, which can attribute a structural order to the material, in a sense telling us how altered it has become at the fault surface. We present data that show the complexity of faulted systems, with structural changes to carbon not always consistent from fault to fault. This adds complexity to our understanding of frictional heating alongside noting the care needed if we are to use Raman as a geothermometer (a method of working out how hot a rock got in the past) in faulted rocks. Key Points: Raman spectroscopy applied to faulted and non‐faulted rocks to assess the nature of peak shift in relation to faulted context A shift in Raman parameters between faulted and non‐faulted samples is exhibited; however, the direction and magnitude of this shift varies Systematic sampling is needed across fault zone study areas to allow for detailed structural analyses